A Trial and Perceptions Assessment of APP-Based Flipped Classroom Teaching Model for Medical Students in Learning Immunology in China - Xingming Ma; Yanping Luo; Lifeng Zhang; Jingqiu Wang; Yaling Liang; Hongjuan Yu; Yufeng Wu; Jiying Tan; Mingqiang Cao (MDPI AG, 2018)
The application-based flipped classroom (APP-FC) is an innovative teaching-learning model that has not been applied and assessed in basic medical curricula teaching in China. The aim of this investigation is to assess students' perceptions to the APP-based flipped classroom (APP-FC) teaching model in an immunology course. The data of this study were collected from second-year medical students (n = 92) at Lanzhou University. One class (n = 50), as a control group, was offered lecture-based learning (LBL), while the other class (n = 42), as the APP-FC group, was given lecture-based instruction and the APP-FC teaching model during September-November 2017. Afterward, the perceptions of students on APP-FC teaching model were evaluated using questionnaires. Students responded that APP-FC improves their motivation (83%) and interest in learning immunology (81%), as well as their self-directed learning skills (81%). Compared to the traditional lecture-based instruction, the APP-FC noticeably improved students' motivation in learning (P = 0.011), self-directed learn skills (P = 0.001), memory abilities (P = 0.009), and problem-solving abilities (P = 0.010). Most medical students' scores (60%) in the final examination were more than 80 points after implementing an APP-FC model as compared to the control group (40%). The majority of students (70%) preferred the APP-FC teaching approach over traditional lecture-based pedagogy. The implementation of the APP-FC teaching model could improve students' learning motivation, self-directed learn skills, and problem-solving abilities, which is a preferable teaching model for medical immunology courses in China.